Speaking for Buddhas : scriptural commentary in Indian Buddhism - Nance, Richard F. (Columbia University Press, 2012)
As with many religious and philosophical traditions, Buddhist intellectual discourse owes its development to a dynamic interplay of primary source material and subsequent interpretation, yet until now Buddhist scholarship has neglected to privilege one crucial series of texts. Commentaries on Buddhist scripture, particularly the sutras, written by seminal thinkers across the history of Indian Buddhism, contain myriad insights into the relationship between textual analysis and ritual practice. Evaluating these commentaries in detail for the first time, Richard F. Nance revisits-and rewrite.